2016
DOI: 10.1055/s-0035-1571252
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Stress Urinary Incontinence: A Systematic Review with Meta-analysis of Randomized Controlled Trials

Abstract: We performed a systematic review and meta-analysis of randomized controlled trials that studied the conservative management of stress urinary incontinence (SUI). There were 1058 results after the initial searches, from which 37 studies were eligible according to previously determined inclusion criteria. For the primary outcomes, pelvic floor muscle training (PFMT) was more efficacious than no treatment in improving incontinence-specific quality of life (QoL) scales (SMD ¼ À1.24SDs; CI 95% ¼ À1.77 to À0.71SDs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
2
45
0
2
Order By: Relevance
“…The morphological changes evidenced in several randomized controlled clinical trials after pelvic floor muscle training allowed to conclude that these exercises are effective in reducing symptoms and/or the stage of POP in middle-aged women, as well as having a potential preventive effect in postpartum prolapse (12) . Recent studies have confirmed that pelvic floor muscle training exercises are effective for treating stress urinary incontinence (SUI) and improving the quality of life of incontinent women (13)(14) . The evidence also indicates that the results are better when pelvic floor exercises are performed weekly under professional supervision (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes evidenced in several randomized controlled clinical trials after pelvic floor muscle training allowed to conclude that these exercises are effective in reducing symptoms and/or the stage of POP in middle-aged women, as well as having a potential preventive effect in postpartum prolapse (12) . Recent studies have confirmed that pelvic floor muscle training exercises are effective for treating stress urinary incontinence (SUI) and improving the quality of life of incontinent women (13)(14) . The evidence also indicates that the results are better when pelvic floor exercises are performed weekly under professional supervision (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The surface or intravaginal electrostimulation of the pelvic floor muscles also obtained good results when compared to no type of treatment, once it improved the indexes of quality of life and the results of the pad test (4) . The vaginal cones, in turn, may be an alternative for the woman that does not contract the pelvic floor muscles properly, even performing exercises for strengthening.…”
Section: Introductionmentioning
confidence: 91%
“…In early study of systematic review, with meta-analysis (4) , one confirmed that the exercises of training of the pelvic floor musculature are affective for the SUI treatment, being this condition the best option for resulting in increase of incontinent women's quality of life. Besides, evidences show that the exercises for the pelvic floor, if performed under professional supervision, at least weekly, presented better results when performed at home, results confirmed in another studies of systematic review (5) .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations